(untitled) (The Research of Medical Science Review, 2024)
Background: Culture negative infective endocarditis (BCNIE) is a diagnostic challenge in the setting of a negative standard blood culture. A major contributing factor to this is previous antibiotic usage which can complicate organism identification. If healthcare resources are limited, understanding the prevalence of previous antibiotic exposure in patients with BCNIE is vital for improving diagnostic and treatment time. Methodology: A cross-sectional, hospital-based study, conducted at National Institute of Cardiovascular Diseases (NICVD), Karachi, on 148 patients who fulfilled Duke's Criteria for culture-negative infective endocarditis (BCNIE). Non-probability consecutive sampling of subjects of both sexes aged 20 to 50 years was done. Data were collected from blood cultures and a history of possible previous antibiotic exposure in patient records. Statistical data was analyzed by SPSS version 26.0 Results; Out of 148 BCNIE patients, mean ± standard deviation of age was noted as 35.16 ± 10.72, among them 66.9% were female while males were accounted for 33.1%. Prior antibiotic therapy had been administered to 56.1%. Fever (80.4%) and heart murmur (68.2%) were the most prevalent symptoms. Neurological complications (33.8%), heart failure (27.0%) occurred among complications and mortality was 23%. Conclusion: The characteristic of former antibiotic treatment as an independent predictor of culture negativity in infective endocarditis has been demonstrated in this study and applied on over half of patients. These Presenting features include fever and heart murmurs and the complications include acute heart failure and neurological manifestations. These findings highlight the need for careful use of antibiotics as well as appropriate diagnostic tools to promote early diagnosis and treatment of infective endocarditis.